OPTIMIZATION OF PROCESS PARAMETERS AND QUALITY RESULTS USING PLASMA ARC CUTTING IN ALUMINUM ALLOY - Hamid, Abdul (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2019)
Plasma cutting is a thermal cutting using a plasma arc that is widely used in metal cutting. CV Kurnia Abadi CNC Plasma Cutting, engaged in CNC plasma cutting based metal cutting services the manufacture of ornaments from steel metal to aluminum. In the field study there were several problems including the quality of cutting and the cost of finishing on aluminum metal. To overcome this problem, the researcher applied the parameter process optimization method by combining the Taguchi method and Gray Relational Analys with the orthoghonal array L9 design selection (34). The material used is aluminum 5083, the response parameters studied are surface roughness and conicity angle. Then compare the results of the research with the actual field data. The results of the study obtained a combination of optimal parameters 90A, 1800mm / s, 3 bars, and 3mm. Parameter contribution is dominated by cutting current 79.42% followed by cutting speed. The difference between the actual data and the optimal combination has increased. While the finishing time was reduced by 2.16 seconds, and finishing costs were minimized to 25.11 rupiah per 100 mm2